2021
DOI: 10.1039/d0ta11146e
|View full text |Cite
|
Sign up to set email alerts
|

H- and J-aggregation inspiring efficient solar conversion

Abstract: Control H- and J-aggregation of non-fullerene acceptor and research their different influence on photovoltaic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…Furthermore, all films demonstrate further bathochromic shift after thermal annealing (TA) process (100 °C for 10 min), indicating the further enhanced J-aggregation molecular assembly. [38,39] Notably, LA16 receives a remarkable bathochromic shift of 17 nm after TA, compared to that of LA17 by 8 nm shift. Therefore, the TA treatment could improve the molecular stacking and should be conductive to enhanced charge transport under appropriate nanoscale networks.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, all films demonstrate further bathochromic shift after thermal annealing (TA) process (100 °C for 10 min), indicating the further enhanced J-aggregation molecular assembly. [38,39] Notably, LA16 receives a remarkable bathochromic shift of 17 nm after TA, compared to that of LA17 by 8 nm shift. Therefore, the TA treatment could improve the molecular stacking and should be conductive to enhanced charge transport under appropriate nanoscale networks.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Wang and coworkers, [39] additional additive could optimize the molecular ordering of F-NFA from face-on and edge-on lamellae to H-and J-type stacking, leading to broadened optical absorption and favorable phase-separated blend morphology, which promotes efficient exciton dissociation at the donor/acceptor interface together with enhanced and balanced charge carrier mobilities. Similarly, He and co-workers [40,41] reported that tuning two aggregation patterns of F-NFAs with different additives or solvent vapor annealing is an effective method for improving the short-circuit current density (J SC ) and the open-circuit voltage (V OC ) of derived devices. As for the UF-NFAs, very few efforts have been made on revealing the effect of molecular self-aggregation properties and crystallization behavior on improving exciton dissociation and charge transport properties, which may prohibit developing new molecular design strategy to make more efficient UF-NFAs.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, developing a strategy to precisely control molecular aggregations to optimize the bulk morphology from molecular level can be challenging. The commonly applied strategies of morphology control, such as the use of different processing solvents [37] and solvent additives, [39][40][41] as well as sequential deposition, [15] rely on kinetically achieving the ideally phase-separated morphology. As reported by Wang and coworkers, [39] additional additive could optimize the molecular ordering of F-NFA from face-on and edge-on lamellae to H-and J-type stacking, leading to broadened optical absorption and favorable phase-separated blend morphology, which promotes efficient exciton dissociation at the donor/acceptor interface together with enhanced and balanced charge carrier mobilities.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Moreover, the substituted alkyl chains or A units in IC2F-BEH-IC2F were modified and the heteroatoms were replaced to improve the photovoltaic properties. [16][17][18][19][20][21] Despite the rapid progress in the improvement of the PCEs of photovoltaic devices based on IC2F-BEH-IC2F derivatives, the trade-off between the short-circuit current density (J SC ) and open-circuit voltage (V OC ) remains a problem. For instance, the modification of central D cores or flanked A units for improved light absorption can increase J SC .…”
Section: Introductionmentioning
confidence: 99%